Influence of Promotion and Brand Image on Maritime Education at STIP Jakarta - Wardoyo Dwi Kurniawan; April Gunawan Malau; Vidya Selasdini (Journal Of Business, Finance, and Economics (JBFE), 2024)
This research investigates the influence of promotional strategies and brand image on the quality of graduates and student applicant interest at the Maritime Institute of Jakarta (STIP). Utilising qualitative methods, the study examines perceptions from maritime professionals, lecturers, and senior cadets who participated in extensive internships. Key findings highlight the effectiveness of digital marketing campaigns, industry collaborations, and alumni engagement in enhancing STIP's visibility and reputation. Stakeholders perceive STIP positively for its practical training and industry-aligned curriculum, contributing to its strong brand image in maritime education. Employers value graduates' technical proficiency, communication skills, and adaptability, underscoring the institute's role in producing competent professionals for the maritime industry. Trends in student applicant interest reveal growing recognition of STIP Jakarta's academic excellence and career opportunities in the maritime sector. Recommendations include sustaining promotional efforts, strengthening brand identity, and adapting curriculum to meet evolving industry needs. This research contributes to understanding the strategic importance of promotion and brand management in vocational education, particularly within maritime institutions.